Characterization of Diarrheagenic Strains of Escherichia coli Isolated From Cattle Raised in Three Regions of Mexico - Navarro, Armando; Cauich-Sánchez, Patricia Isidra; Trejo, Alejandro; Gutiérrez, Alvaro; Díaz, Sylvia Paz; Díaz C., Martha; Cravioto, Alejandro; Eslava, Carlos (Frontiers in Microbiology, 2018)
Intestinal infections represent an important public health concern worldwide. Escherichia coli is one of the main bacterial agents involved in the pathogenesis of different diseases. In 2011, an outbreak of hemorrhagic colitis (HC) and hemolytic uremic syndrome (HUS) in Germany was related to a non-O157 STEC strain of O104:H4 serotype. The difficulty in identifying the origin of the bacteria related to the outbreak showed the importance of having epidemiological information from different parts of the world. The aim of this study was to perform a retrospective analysis to determine if E. coli strains isolated from cattle from different locations in Mexico have similar characteristics to those isolated in other countries. Samples obtained in different years from 252 cows belonging to 5 herds were analyzed. A total of 1,260 colonies were selected from the 252 samples, 841 (67%) of which corresponded to E. coli and 419 (33%) to other enterobacteria. In total, 78% (656) of the E. coli strains could be serotyped, of which 393 (59.9%) belonged to 5 diarrheagenic (DEC) pathotypes. Serotyping showed STEC (40.7%) and ETEC (26.7%) strains were more common. PCR assays were used to determine the presence of STEC (eae, stx1, stx2, ehxA) and EAEC (aatA, aggR, aapA) genes, and phylogenetic groups. The results showed that 70 strains belonging to 23 serogroups were stx1 and stx2 positive, while 13 strains from the O9 serogroup were ehxA, aggR and eae positive. Phylogenetic analysis showed 58 (82.9%) strains belonged to A and B1 commensal phylogroups and 12 (17.1%) to B2, D and E virulent phylogroups. An assay to evaluate cross-antigenic reactivity in the serum of cattle between K9 capsular antigen and O104 LPS by ELISA showed similar responses against both antigens (p>0.05). The antimicrobial sensitivity assay of the strains showed resistance to AM, CEP, CXM, TE, SXT, cephalosporins and fluoroquinolones. The results show that cattle are carriers and potential transmitters of STEC and ETEC strains containing virulence genes. Epidemiological retrospective studies in different countries are of great help for identifying virulent bacterial strains with the potential to cause outbreaks that may have epidemiological impact in susceptible countries.